Foundlings : lesbian and gay historical emotion before Stonewall - Nealon, Christopher S. (Christopher Shaun), 1967- (Series Q., 2001)
An examination of the concept of orphandom in gay and lesbian experience, and how it has been instrumental in defining and mobilizing queer subcultures.